2009
DOI: 10.1590/s1806-83242009000400018
|View full text |Cite
|
Sign up to set email alerts
|

The role of polymerization cycle and post-pressing time on tooth movement in complete dentures

Abstract: This study analyzed the influence of polymerization cycle and post-pressing time on tooth movement in complete dentures. Forty maxillary complete dentures were fabricated and randomly assigned to 8 groups (n = 5); the polymerization cycle (conventional long cycle in water bath, fast cycle in boiling water, and by microwave energy) and the post-pressing time (immediate and 6 hours) were varied. Metal reference pins were placed on the incisal border of the central incisors (RI and LI), on the buccal cusp of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Con respecto al yeso como material de prueba, los valores de distorsión variaron con respecto a la fuerza aplicada, con un comportamiento asociado a la composición misma del material empleado 1 . Es evidente que durante la compresión existirán movimientos dentales horizontales 37 , independientes de la forma de polimerización de la resina acrílica en microondas o por sistema convencio-nal 23 , recomendando un lento proceso de enfriamiento después del procesamiento de las muflas, lo que evitaría un alto estrés residual, generado por una expansión térmica gradual entre modelo y mufla; garantizando con ello mayor equilibrio de las prótesis dentales totales en la cavidad oral, menor reabsorción de la cresta residual y por consecuencia mayor comodidad para el paciente 38 .…”
Section: Discussionunclassified
“…Con respecto al yeso como material de prueba, los valores de distorsión variaron con respecto a la fuerza aplicada, con un comportamiento asociado a la composición misma del material empleado 1 . Es evidente que durante la compresión existirán movimientos dentales horizontales 37 , independientes de la forma de polimerización de la resina acrílica en microondas o por sistema convencio-nal 23 , recomendando un lento proceso de enfriamiento después del procesamiento de las muflas, lo que evitaría un alto estrés residual, generado por una expansión térmica gradual entre modelo y mufla; garantizando con ello mayor equilibrio de las prótesis dentales totales en la cavidad oral, menor reabsorción de la cresta residual y por consecuencia mayor comodidad para el paciente 38 .…”
Section: Discussionunclassified
“…To reduce this undesirable effect on the denture procedure, different denture flasking methods, polymerisation techniques and denture base materials have been studied 11–15,19 ; however, recent reports have not revealed statistical differences among tooth displacements as a consequence of different polymerisation methods during complete denture processing 6,25 . Few laboratory procedures can minimise tooth displacement; however, some studies have shown that this displacement is, unfortunately, not eliminated completely 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Post-pressing time [21] 6 hour post-pressing time had no significant advantage over the usual 45mins to 1 hour of bench curing.…”
mentioning
confidence: 81%
“…Teeth displacement can occur in any direction; antero-posterior, transverse or vertical. It can also occur due to several other factors such as base thickness [8,9], palatal form [1,10], flask closure [5,11], investing media and procedure [12][13][14][15][16][17][18][19], polymerization techniques [15], flask cooling method [11,20], post-pressing time [5,21], water storage [20,22], monomer-polymer ratio [23] and wax instability [24].…”
Section: Introductionmentioning
confidence: 99%